Printable Optical Filters for Visible Optical Communications - André, Paulo (2018)
The design, production and characterization of tailored printable optical filters for visible optical communications are demonstrated. As result, the average color difference between the specified and the produced filters is 32.6, quantified in terms of CIELAB coordinates.